2021
DOI: 10.21608/ejchem.2021.71259.3568
|View full text |Cite
|
Sign up to set email alerts
|

Flammability properties of polyvinyl alcohol containing new flame retardant system

Abstract: In this work, graphite (G), ammonium iron (II) sulfate (AFS) and aluminium nitrate were added to polyvinyl alcohol (PVA) at 25% loading level to improve its flame retardancy. In addition, PVA/(G+AFS+AN) composite was prepared. The flammability and smoke density of PVA composites were evaluated by UL94 flame chamber, limiting oxygen index (LOI) and smoke density chamber. Vertical flame spread test (UL94V) indicated that PVA composites achieved V0 class in PVA/(G+AFS+AN)and PVA/AFS samples. Horizontal burning ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When the temperature exceeds 400°C, PVA backbone degradation is observed. 8 PVA15 composite is also decomposing through two stages. In addition, the values of T 10% , T 50% , T 1max , and T 2max of PVA15 composite are lower than the corresponding values in pure polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the temperature exceeds 400°C, PVA backbone degradation is observed. 8 PVA15 composite is also decomposing through two stages. In addition, the values of T 10% , T 50% , T 1max , and T 2max of PVA15 composite are lower than the corresponding values in pure polymer.…”
Section: Resultsmentioning
confidence: 99%
“…1 Physical blending of PVA with flame retardant materials, which can be organic or inorganic compounds, is a widely used method to prepare flame-retarded PVA. Makhlouf et al 8 added ammonium iron (II) sulfate (AFS) to PVA to improve its flame retardancy. The authors reported that the addition of 25 wt% (AFS) to PVA enhanced its LOI to 26.1%, and the samples achieved V0 in the vertical flame spread test.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with these materials, poly­(vinyl alcohol) (PVA) has garnered significant attention in recent years due to their exceptional advantages, including low cost, good chemical stability, outstanding biocompatibility, and environmental sustainability. However, the limitations of pure PVA include high flammability , (limited oxygen index (LOI) ∼ 19.8%) and superhydrophilicity due to its organic framework composed of abundant hydroxyl groups, which restricts its feasibility in many practical applications. Extensive research has been conducted to improve the flame retardancy of PVA aerogels, particularly by preparing organic/inorganic composite aerogels through the addition of inorganic fillers .…”
Section: Introductionmentioning
confidence: 99%